Hand-Dug Underreamed Piles At Embankment Place, London - W. J. Grose (Deep Foundations Institute, 1989)
The Embankment Place office development over the platforms of Charing Cross Railway Station in London has presented many interesting and unusual problems to the engineers involved with the project. The main structure is supported on widely-spaced columns which penetrate the station platforms and underlying vaults, calling for high capacity foundations built in severely restricted spaces. Hand-dug underreamed piles were chosen. Whilst a conventional design approach was taken to size the piles, a detailed appraisal of ground movements was made to explore the effects of the new building loads on the existing foundations, not only beyond the site perimeter but also those amongst the new foundations. Before construction of the pile proper could take place, it was necessary to sink a caisson through the upper unstable and water-bearing soils. This being identified as a high-risk item, a full-scale trial was carried out prior to embarking on the main works. The twenty-one hand-dug piles were 2.5m diameter, over 30m deep and belled out to between 4.5m and 6.6m.